Humanistic Curriculum Development Model Typical of Anak Langit Islamic Elementary School (ALIEs) in Bandung, West Java - Siti Nurhikmah; Sandy Sandy; Mohamad Erihadiana (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
This study aims to describe ALIES's distinctive curriculum and the development of a humanistic curriculum in ALIES. Humanistic curriculum development is carried out to develop students themselves and realize themselves according to their potential. This study used a qualitative approach with an analytical descriptive method. Data sources consist of primary data sources and secondary data sources. Data collection techniques were carried out by means of interviews, observation and documentation. The results of this study indicate that ALIES's typical curriculum is the Billingual System, Psychological Approach and Tahsin Tahfidz Qur'an. The development of ALIES's unique humanistic curriculum has the goal of welcoming the future of students so that they are able to survive in a changing environment. The development of a humanistic curriculum is developed based on the Al-Qur'an and As-Sunnah; apply metacognitive so that students are able to prepare their life goals. The implementation of curriculum development starts from the development of every educator who teaches by participating in various trainings. Supporting factors in the development of a typical curriculum are an environment that has emphasized the importance of implementing a bilingual system, TTQ learning, educators who come from English graduates and psychology institutions in schools. The inhibiting factor is the lack of educators. The effect of developing a humanistic curriculum for students can be shown that the ability to understand English is grade 1 (20%), grade 2 (40%), grade 3 (60%) and grade 4 (80%). The influence of the psychological approach for students is being able to behave politely to educators, friends and parents, being happy while studying in class, being able to control their emotions and develop their potential. The effect of TTQ on students is that the ability to read the Koran for each individual increases, their memorization increases and students become accustomed to reading the Qur’an